Begal Anak; Pemenuhan Hak dan Lembaga Pembinaan Khusus Anak Kelas II A Bandar Lampung - Eka Intan Putri (Cepalo, 2019)
Child protection is all activities to ensure the implementation of the guaranteed rights of children, including the rights of children as criminals. Legalization is a crime and deviation in society that also violates social norms, wherever and done by anyone. It is often heard that there are still complaints from families and convicted children regarding alleged violations of the implementation of the rights of criminal child rights in the "Special Child Development Institution (LPKA)", even criminal children are also vulnerable to violence from fellow criminals.In this research, the writer will use empirical and normative juridical approaches. This study will use secondary and primary data, secondary data consisting of primary, secondary and tertiary legal materials. This research will use qualitative data analysis. From the results of the study it was concluded that the implementation of children's rights as criminal offenses in LPKA Class II Bandar Lampung, referring to Law Number 11 of 2012 concerning the Criminal Justice System for Children, and guided by Law Number 12 of 1995 concerning Correctional Facilities. Of the 13 (thirteen) children's rights as criminal offenders begal, there are 11 (eleven) rights of criminal offenders that have been implemented even though it is not yet perfect. However, there are still obstacles, namely inhibiting factors from the community and law enforcement officers, namely there is no family concern for criminal children, in terms of health, education, and guidance, while fostering criminal children is completely surrendered to officers in LPKA, and the lack of coordination between Related agencies are the District Attorney and the District Court with the Special Child Development Institute (LPKA).